Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1055/s-2006-923776
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Energy Expenditure in Competitive Swimming Strokes

Abstract: The purpose of this study was to measure and compare the total energy expenditure of the four competitive swimming strokes. Twenty-six swimmers of international level were submitted to an incremental set of 200-m swims (5 swimmers at Breaststroke, 5 swimmers at Backstroke, 4 swimmers at Butterfly and 12 swimmers at Front Crawl). The starting velocity was approximately 0.3 m x s (-1) less than a swimmer's best performance and thereafter increased by 0.05 m x s (-1) after each swim until exhaustion. Cardio-pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 20 publications
7
91
0
4
Order By: Relevance
“…Previous studies have demonstrated that front crawl and backstroke techniques were more economical than butterfly and breast stroke and that front crawl was more economical than backstroke at slower and maximal speeds [9,13,14]. Our results are in line with these studies and confirmed higher energy expenditure values during backstroke test than during front crawl test.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous studies have demonstrated that front crawl and backstroke techniques were more economical than butterfly and breast stroke and that front crawl was more economical than backstroke at slower and maximal speeds [9,13,14]. Our results are in line with these studies and confirmed higher energy expenditure values during backstroke test than during front crawl test.…”
Section: Discussionsupporting
confidence: 82%
“…Energy expenditure is a widely used parameter in swimming science as an indicator of performance [8][9][10].Thermal imaging has been used in cycling to explore the relationship between skin temperature and gross efficiency [5] but, to our knowledge, no study has used infrared thermography to investigate the possible relationship between energy expenditure and skin temperature in swimming activities. The aims of this research are to study the influence of two different swimming techniques in the Tsk distribution and analyse the relationships between Tsk and energy expenditure in national level competitive swimmers.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, enlarging the field of evaluation, the four competitive swimming techniques were studied by this Portuguese research group, observing the primary outcomes: (i) significant relationships between energy expenditure and intra-cycle variation, C and velocity (Barbosa et al, 2005a); (ii) that front crawl was the most economic technique, followed by backstroke, butterfly, and breaststroke (Barbosa et al, 2006); and (iii) the manipulation of the SR and SL might be one of the factors through which energy cost can be altered for a given velocity (Barbosa et al, 2008). As competitive distances vary in swimming, Seifert et al (2010) studied the effect of swimming speciality (sprinters vs. long distance swimmers) in C (and in motor organization), observing that both groups had an increase in C of swimming with increasing velocity.…”
Section: Methods Authorsmentioning
confidence: 99%
“…Thus, the PSwT was proven reliable when evaluated on different days by different evaluators, presenting possibilities of application in the aquatic environment to be associated with a swimming test 11 . Additionally, it was compared to a direct oximetry method showing the same performance connection 12 , and finally its equation was applied to a practical situation through the 400 MF test where using HR, distance, and time to determine the aptitude of non-expert swimmers, both obtained a high association 12,32,33 . The following were considered to be limitations of the study: (i) it was not possible to evaluate the biomechanical aspects during both tests, since when swimmers reached their maximum performance, they suffered alterations in the length and number of strokes; (ii) the results described here are valid only for non-expert swimmers, which means another researcher should refrain from applying this test to elite swimmers; (iii) it was not possible to evaluate the test's sensibility through an exercise program which could then utilize the test to verify aerobic power.…”
Section: Discussionmentioning
confidence: 99%